2019
DOI: 10.1016/j.scitotenv.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of antibiotics by modified vacuum-UV based processes: Mechanistic consequences of H2O2 and K2S2O8 in the presence of halide ions

Abstract: In this work, the degradation of cefalexin, norfloxacin, and ofloxacin was examined via various advanced oxidation processes (AOPs). Direct photolysis by ultraviolet (UV) and vacuum ultra violet (VUV) was less effective for the degradation of fluoroquinolone antibiotics such as norfloxacin and ofloxacin than that of cefalexin. Both hydrogen peroxide (H 2 O 2) and potassium persulfate (K 2 S 2 O 8) assisted UV/VUV process remarkably enhanced fluoroquinolone degradation. The addition of K 2 S 2 O 8 was superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Natural processes are not always strong enough to treat effluents polluted with antibiotics, but some photochemical advanced oxidation processes (AOPs) have been shown to be useful to treat FQ (Guinea et al, 2009;Feng et al, 2018;Feng et al, 2016;Van Doorslaer et al, 2013;Sun et al, 2019). AOPs are able to generate powerful transitory reactive species, mainly hydroxyl radicals (•OH) (Glaze et al, 1987;Legrini et al, 1993), but other species can also be involved (An et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Natural processes are not always strong enough to treat effluents polluted with antibiotics, but some photochemical advanced oxidation processes (AOPs) have been shown to be useful to treat FQ (Guinea et al, 2009;Feng et al, 2018;Feng et al, 2016;Van Doorslaer et al, 2013;Sun et al, 2019). AOPs are able to generate powerful transitory reactive species, mainly hydroxyl radicals (•OH) (Glaze et al, 1987;Legrini et al, 1993), but other species can also be involved (An et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results were similar to the reported comparison of clonidine (CLD) removal by UV/H 2 O 2 and PDS that UV/H 2 O 2 exhibited better performance than UV/PDS (Xiao et al, 2020b ). It was different from the removal of carbamazepine (CBZ), 2,4-bromophenol, ofloxacin (OFX), ibuprofen, and cylindrospermopsin (CYN) by UV/H 2 O 2 and UV/PDS that UV/PDS showed a better performance than UV/H 2 O 2 (He et al, 2013 ; Yang et al, 2017 ; Luo et al, 2019 ; Sun et al, 2019 ; Xiao et al, 2020a ). Production rates of radicals from UV/peroxide processes mainly depend on molar extinction coefficients and photolysis quantum yields of peroxides.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of UV/PDS and UV/H 2 O 2 was made on decontamination efficiencies. UV/PDS showed a better performance than UV/H 2 O 2 on the removal of carbamazepine (CBZ), 2,4-bromophenol, ofloxacin (OFX), ibuprofen, and cylindrospermopsin (CYN) (He et al, 2013 ; Yang et al, 2017 ; Sun et al, 2019 ; Luo et al, 2019 ; Xiao et al, 2020a ). In studying the degradation of beta amide antibiotics, TOC removal by UV/PDS was slightly better than that by UV/H 2 O 2 (He et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The experiments demonstrated that the peroxone (O 3 /H 2 O 2 ) method was better than ozonation alone, and higher pH was preferred for the removal of the Direct Red 80 dye in both processes. Sun, Cho, et al (2019) used several AOPs to remove cefalexin, norfloxacin, and ofloxacin. It was found that direct photolysis by ultraviolet (UV) and vacuum ultraviolet (VUV) was more effective to remove cefalexin than norfloxacin and ofloxacin.…”
Section: Annual Literature Reviewmentioning
confidence: 99%